THE WAYS OF IMPROVE AND ATTRACT INVESTMENTS IN REGION (THE CASE OF ANDIJAN REGION) - Radjabov Bunyod Abduhalilovich (Research Parks Publishers, 2020)
This article explores the theoretical foundations of increasing investment attractiveness in the regions. The investment attractiveness of Andijan region is analyzed. Based on the results of the analysis, proposals and recommendations aimed at increasing the attractiveness of the investment climate in Andijan region were developed.